Effects of Pouring Temperature on Microstructure and Mechanical Properties of the A356 Aluminum Alloy Diecastings - Li,Ming (2020)
Abstract Diecastings of the A356 aluminum alloy were produced by rheo-diecasting (RDC) and High pressure die casting (HPDC), the microstructures of primary solidification, secondary solidification and eutectic Si of diecastings with different pouring temperature were explored and the mechanical properties of different parameters were tested. The result shows that the primary α-Al grains in RDC with self-inoculation method (SIM) are smaller and rounder than the dendrite structure in HPDC. During the RDC process, the amount of primary α-Al grains, average grain size and the lamellar spacing of the eutectic Si increase with the decrease of the melt treatment temperature. While the average grain size and the shape factor are gradually increasing with the increase of melt treatment temperature. As a result, RDC can significantly improve the mechanical properties of the A356 aluminum alloy compared with HPDC, the mechanical properties are optimal at 600°Cwith the tensile strength and elongation are 268.67MPa and 6.8%, respectively.